Conditions for innovation in Brazil: A review of key issues and policy challenges - Pluvia Zuniga; Fernanda De Negri; Mark Andrew Dutz; Dirk Pilat; André Rauen (Institute for Applied Economic Research (ipea), 2016)
This paper examines Brazil's position in research, technology transfer and innovation activities relative to peer economies and a selected group of developed countries. It reviews the governance of the research and innovation systems, the current policy landscape, and the results achieved by current policy programs. Based on this analysis and supplemented by discussions from a national seminar on Brazil's innovation policies, the paper identifies key outstanding challenges to foster a more effective national innovation system and improved innovation performance by the business sector. The paper concludes with suggestions for public policy reforms for business innovation in Brazil, focusing above all on more effective market competition as a necessary condition for state support to innovation to succeed. Other priority areas include improved public research and industry collaboration, greater firm innovation and demand effectiveness, better policy coordination, and regular Public Expenditure Reviews and other forms of monitoring and evaluation. A previous version of this paper served as background for a national seminar on innovation for productivity growth held in Brasilia on July 1-2, 2015 organized jointly by Ipea, the Brazilian Industrial Development Agency (ABDI), the World Bank, and the Organisation for Economic Co-operation and Development (OECD). This version integrates key messages from the discussions, plus helpful comments received from Xavier Cirera, Paulo Correa, Donato De Rosa, Martin Raiser and Frank Sader. The views herein expressed are entirely those of the authors. They do not necessarily represent the views of their institutions.
Keywords: O38; L16; D24; 330; Innovation policy; Brazil; productivity